Biologic and Clinical Analysis of Childhood Gamma Delta T-ALL Identifies LMO2/STAG2 Rearrangements as Extremely High Risk - Kimura, Shunsuke; Park, Chun Shik; Montefiori, Lindsey E; Iacobucci, Ilaria; Pölönen, Petri; Gao, Qingsong; Arnold, Elizabeth D; Attarbaschi, Andishe; Brown, Anthony; Buldini, Barbara; Caldwell, Kenneth J; Chang, Yunchao; et al. (Cancer discovery, 2024)
Acute lymphoblastic leukemia expressing the gamma delta T-cell receptor (γδ T-ALL) is a poorly understood disease. We studied 200 children with γδ T-ALL from 13 clinical study groups to understand the clinical and genetic features of this disease. We found age and genetic drivers were significantly associated with outcome. γδ T-ALL diagnosed in children under 3 years of age was extremely high-risk and enriched for genetic alterations that result in both LMO2 activation and STAG2 inactivation. Mechanistically, using patient samples and isogenic cell lines, we show that inactivation of STAG2 profoundly perturbs chromatin organization by altering enhancer-promoter looping, resulting in deregulation of gene expression associated with T-cell differentiation. High-throughput drug screening identified a vulnerability in DNA repair pathways arising from STAG2 inactivation, which can be targeted by poly(ADP-ribose) polymerase inhibition. These data provide a diagnostic framework for classification and risk stratification of pediatric γδ T-ALL. Significance: Patients with acute lymphoblastic leukemia expressing the gamma delta T-cell receptor under 3 years old or measurable residual disease ≥1% at end of induction showed dismal outcomes and should be classified as having high-risk disease. The STAG2/LMO2 subtype was enriched in this very young age group. STAG2 inactivation may perturb chromatin conformation and cell differentiation and confer vulnerability to poly(ADP-ribose) polymerase inhibition.
Keywords: Infant; Humans; kojenec; dítě; Child; lymfoblastická leukemie-lymfom z prekurzorových T-buněk; Female; adaptorové proteiny signální transdukční; lidé; Adaptor Proteins, Signal Transducing; Precursor T-Cell Lymphoblastic Leukemia-Lymphoma; Cell Cycle Proteins; protoonkogenní proteiny; předškolní dítě; ženské pohlaví; Male; proteiny buněčného cyklu; Proto-Oncogene Proteins; Gene Rearrangement; genová přestavba; mužské pohlaví; LIM Domain Proteins; Child, Preschool; proteiny s doménou LIM